2020
DOI: 10.21203/rs.3.rs-62968/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Depression Symptoms and Associated Sociodemographic and Clinical Correlates among Syrian Refugees in Lebanon

Abstract: Background: Since the outbreak of the Syrian war in 2011, close to 6 million Syrian refugees have escaped to Syria’s neighbouring countries, including Lebanon. Evidence suggests rising levels of mental health disorders among Syrian refugee populations. Yet, to the best of our knowledge, large-scale studies addressing the mental health of adult Syrian refugees in Lebanon are lacking.Aims: We examined the prevalence of depression symptoms, which represent a common and debilitating mental health disorder among Sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Comparable and higher prevalence were reported among Palestinian and Syrian refugees in Lebanon (72,(87)(88)(89)(90) . A strong relationship was observed between poor maternal mental health, food insecurity, and a high crowding index in our findings.…”
Section: Discussionmentioning
confidence: 83%
“…Comparable and higher prevalence were reported among Palestinian and Syrian refugees in Lebanon (72,(87)(88)(89)(90) . A strong relationship was observed between poor maternal mental health, food insecurity, and a high crowding index in our findings.…”
Section: Discussionmentioning
confidence: 83%
“…A nationally representative study among the Lebanese population showed lifetime prevalence of 12.6% for mood disorders, and 25.8% for anxiety ( Karam et al, 2008 ). A recent survey study among Syrian displaced people revealed a point prevalence of moderate to severe depression symptoms of 22% ( Naal et al, 2021 ). There is a large mental health treatment gap.…”
mentioning
confidence: 99%
“…Forty-two studies focused on major depressive disorder or depressive symptoms (Acarturk et al, 2018, 2021; Ahmad et al, 2021; Böge et al, 2020; Borho et al, 2020; Braun-Lewensohn et al, 2019; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; Demir et al, 2020; Euteneuer & Schäfer, 2018; Fuhr et al, 2019; Gammouh et al, 2015; Georgiadou et al, 2018, 2020; Javanbakht et al, 2019; Mahmood et al, 2019; Marwa, 2016; McGrath et al, 2020; Mohammad et al, 2018; M’zah et al, 2019; Naal et al, 2021; Naja et al, 2016; Oda et al, 2021; Okenwa-Emegwa et al, 2019; Poole et al, 2018; Rizkalla & Segal, 2018, 2019; Röhr et al, 2020; Schlechter et al, 2021; Sengoelge et al, 2019; Sevinc et al, 2021; Sim et al, 2018; Stevenson et al, 2019; Tekeli-Yesil et al, 2018; Tinghög et al, 2017; Uygun, 2021; Woltin et al, 2018; Yalim, 2021). The most used instrument was the Hopkins Symptom Checklist 25-items (HSCL-25), and the prevalence of positive screening results ranged from 34.7% to 59.4%.…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%